2010
DOI: 10.1016/j.strusafe.2010.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Damage identification study of a seven-story full-scale building slice tested on the UCSD-NEES shake table

Abstract: A full-scale seven-story reinforced concrete building section was tested on the UCSD-NEES shake table during the period October 2005 -January 2006. The shake table tests were designed to damage the building progressively through four historical earthquake records. At various levels of damage, ambient vibration tests and low amplitude white noise base excitations with root-mean-square accelerations of 0.03g and 0.05g were applied to the building, which responded as a quasi-linear system with parameters evolving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
120
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(142 citation statements)
references
References 19 publications
11
120
0
Order By: Relevance
“…Specifically, the two measures of fit are given by experimentally identified and estimated mode shapes for the r -th mode. Alternative measures of fit can easily be used and found in literature [18][19][20][21][22].…”
Section: Modal Residualsmentioning
confidence: 99%
“…Specifically, the two measures of fit are given by experimentally identified and estimated mode shapes for the r -th mode. Alternative measures of fit can easily be used and found in literature [18][19][20][21][22].…”
Section: Modal Residualsmentioning
confidence: 99%
“…Outputonly system identification methods, which have been successfully applied for system identification of linear systems (He et al 2009;Moaveni et al 2011), are based on the assumption of a broadband (ideal white-noise) input excitation. However, in this set of experiments, the white-noise base excitation inputs were significantly modified by the shake table system dynamics, and consequently, the table motions did not satisfy the broadband assumption as illustrated in Fig.…”
Section: System Identification Of the Infilled Framementioning
confidence: 99%
“…Furthermore, actual construction practices often cannot be reproduced in small-/medium-scale test specimens. The few instances of successful application of FE model updating methods for the condition assessment of large-scale structures include the damage identification studies on the Z24 Bridge in Switzerland (Teughels and De Roeck 2004), the use of dynamic strain measurements from fiber optic sensors for FE model updating of the Tilff Bridge (Reynders et al 2007), the use of a neural network method based on modal frequencies and a validated FE model to identify the stiffness reduction in a one-third-scaled one-story concrete frame (Zhou et al 2007), and FE model updating based on identified modal properties of a full-scale composite beam (Moaveni et al 2008) and a full-scale seven-story RC shear wall building slice (Moaveni et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For the second group, the measure of fit I 2 ðyÞ is selected to represent the difference between the measured and the model predicted mode shape components for all modes. Specifically, the two measures of fit are given by Alternative measures of fit [3,[19][20][21][22] can easily be accommodated in the proposed formulation. In particular, it is straightforward to show that…”
Section: Modal Residualsmentioning
confidence: 99%
“…This case study demonstrates that unidentifiability issues arise in updating FE models with a large number of DOFs, build for realistic structures and using real measurements. As it is noted in Figure 8(a), the unidentifiable solutions corresponding to the flat horizontal portion (points [12][13][14][15][16][17][18][19][20] in the objective space and the associated manifold in Figure 8(b) are readily estimated by the NBI method. From the engineering point of view, the most important point from this flat portion is the most left point 12 in Figure 8(a) since all other points in the flat portion deteriorate the fit in the objective function J 1 ðyÞ without altering the fit in J 2 ðyÞ.…”
Section: Unidentifiability Issuesmentioning
confidence: 99%